Crystallographic analysis and phasing of iron‐assimilating protein 1 (FEA1) from Chlamydomonas reinhardtii. Issue 5 (5th May 2021) - Juniar, Linda; Adlfar, Vida; Hippler, Michael; Tanaka, Hideaki; Kurisu, Genji
Abstract : In Chlamydomonas reinhardtii, iron levels are strictly controlled by iron‐assimilating protein 1 (FEA1). Recombinant FEA1 protein was successfully purified and crystallized by hanging‐drop vapor diffusion. The phase problem was solved by the native sulfur SAD method using long‐wavelength X‐rays (2.7 Å). Laser‐cutting technology was used to increase the signal‐to‐noise ratio and derive an initial structure. Abstract : As an essential component of protein cofactors, iron is important for all photosynthetic organisms. In Chlamydomonas reinhardtii, iron levels are strictly controlled by proteins such as iron‐assimilating protein 1 (FEA1). This periplasmic protein is expressed under conditions of iron deficiency, but its mechanisms of function remain unknown. Because FEA1 has no amino‐acid similarity to protein structures in the Protein Data Bank, its crystal structure cannot be solved by molecular replacement. Here, recombinant FEA1 protein lacking the N‐terminal signal sequence was successfully purified and crystals of apo FEA1 were obtained by hanging‐drop vapor diffusion. Neither selenomethionine substitution nor heavy‐atom derivatization was successful; therefore, the phase problem of FEA1 crystals was solved by the native sulfur SAD method using long‐wavelength X‐rays (2.7 Å). Laser‐cutting technology was used to increase the signal‐to‐noise ratio and derive an initial structure. This study will lead to further structural studies of FEA1 to understand its function and its links to the iron‐assimilation pathway.